On the improved plasma confinement in toroidal systems. Measuring of the plasma density inhomogeneties near the gas valve - Petrov, A.A.; Petrov, V.G.; Popryadukhin, A.P. (Вопросы атомной науки и техники, 2007)
Comparison of plasma density increase was carried out in outer and inner channels of the interferometer in T-11M tokamak. There were two cases of gas puffing: by outer valve or upper one. Amplitude of difference of the plasma density increase consisted of 9% near the outer valve. Perturbation of the electric potential eΦ1/Te can have similar value. This perturbation can lead to appearance of the additional losses.